DIGITAL TECHNOLOGY INNOVATION IN SUPPORTING EARLY DETECTION OF CERVICAL CANCER: A SYSTEMATIC REVIEW OF SMARTPHONE APPLICATIONS, DIGITAL EDUCATION, AND TELEMEDICINE TRAINING (Proceedings of the International Conference on Public Health, 2026)
Cervical cancer is one of the leading causes of death among women worldwide, particularly in developing countries. Low health literacy, a shortage of trained healthcare professionals, and limited access to modern medical facilities are significant barriers to early detection. Technological innovations, including smartphone-based applications, digital education via social media, and telemedicine-based training, offer promising solutions to enhance access to and quality of healthcare services. This study is a systematic review conducted following the Preferred Reporting Items for Systematic Reviews and Meta- Analyses (PRISMA) guidelines. Data were retrieved from multiple electronic databases, including PubMed, ScienceDirect, and the Cochrane Library. Studies meeting the inclusion criteria were analyzed to assess the effectiveness of digital technologies in supporting early cervical cancer detection. Data extraction and risk assessment were performed independently by two researchers. Eight selected studies demonstrated the effectiveness of technology-based interventions in improving health literacy, diagnostic accuracy, and healthcare worker competence. Digital education delivered via platforms such as WhatsApp and Facebook has been shown to enhance knowledge and attitudes among women of reproductive age regarding early cervical cancer detection. Smartphone-based applications utilizing artificial intelligence (AI) achieved an accuracy rate of up to 93.8%, while telemedicine-based mentorship programs improved screening quality, with the Kappa coefficient increasing from 0.64 to 0.79. Technological innovations involving smartphone applications, digital education, and telemedicine mentorship have significant potential to overcome barriers to early cervical cancer detection. These strategies could be integrated into national healthcare programs to expand screening coverage and improve effectiveness, particularly in resource-limited settings.
Keywords: cervical cancer; smartphone applications; digital education; telemedicine; early detection